Design and Evaluation of Vacuum Central Drum Seed Metering Device - Baolong Wang; Yi Na; Jian Liu; Zaiman Wang (Applied Sciences, 2022)
For the purpose of reducing the number of conventional seed-metering devices and high demand for vacuums, this study designed a vacuum central drum seed-metering device, that is intended to replace multiple seed-metering devices with one, which is comprised of the inner and outer drum. This can be replaced with different diameters of suction holes, ventilation housing, seeding tube, agitating devices, seed box, and seed-cleaning devices, etc. A hybrid rice seed Jingliangyou 1212 was applied as an experimental material, and a JPS-12 computer vision metering device test bench was used to test singular-factor and multi-factor seeding performance of the seed-metering device. The singular-factor performance test of the metering device was conducted under negative pressure of seed suction in the range of 1∼1.5 kPa, at the metering device rotation speed of 10∼60 rpm, with diameters of inlet holes being 2 mm (chamfer: 45°), 2, and 1.5 mm, respectively. The number of seeds was counted by a sucking hole under different factor combinations. The multi-factor test was carried out by rotation rate, negative pressure, and types of sucking holes. A rate of 2 ± 1 rice seed per sucking hole is regarded as the qualified standard. It shows that the qualification rate (2 ± 1 rice seed per sucking hole) of seed suction can reach 97.4% under a combination of metering device rotation speed of 30 r/min, negative pressure of 1.0 kPa, and suction hole diameters of 1.5 mm. High-speed photography was used to study the trajectory of seed-metering at different rotation rates, a locomotive axis was applied to fit the motion curve, and 3D-printing was used to make the seed-metering tube so that the seed collisions could be reduced. This study provides evidence for further optimizing the performance of the vacuum central drum direct-seeding machine for hybrid rice.